Tricuspid annular plane systolic excursion inaccuracy to assess right ventricular function in patients with previous tricuspid annulopasty. (15th November 2016) - de Agustin, Jose Alberto; Martinez-Losas, Pedro; de Diego, Jose Juan Gomez; Mahia, Patricia; Marcos-Alberca, Pedro; Nuñez-Gil, Ivan Javier; Rodrigo, Jose Luis; Luaces, Maria; islas, Fabian; Garcia-Fernandez, Miguel Angel; Macaya, Carlos; de Isla, Leopoldo Perez
Abstract: Objetives: The clinical and prognostic usefulness of tricuspid annular plane systolic excursion (TAPSE) is well established. However, the ability of TAPSE to assess right ventricular (RV) function in patients with previous tricuspid valve annulopasty is controversial. This study examined the TAPSE suitability in patients with previous tricuspid valve annuloplasty using right ventricular fractional area change (RVFAC) as reference method. Methods: We retrospectively analyzed 53 patients who underwent tricuspid valve annuloplasty at our hospital between 2013 and 2016. TAPSE and RVFAC were obtained in preoperative and postoperative periods using standard methodology. Results: Mean age was 68 ± 12 years and 34 patients (64.1%) were women. TAPSE decreased significantly after surgery in comparison with pre-surgical values (17 ± 4.2 Vs 12.9 ± 4.1 mm, p < 0.001). On the contrary, RVFAC did not change significantly after surgery (37 ± 9.2 Vs 36.2.9, p = 0.25). The correlation between RVFAC and TAPSE was better in the preoperative (r = 0.63, p < 0.0001) than in the postoperative period (r = 0.38, P = 0.005). Good intra- and interobserver agreement for TAPSE and RVFAC was obtained, with intraclass correlation coefficients of 0.97 and 0.92 for TAPSE; and 0.90 and 0.85 for RVFAC, respectively. Conclusions: These findings suggest that TAPSE is not suitable after tricuspid valve annuloplasty and it leads to an underestimation of RV systolic function. It seems to be appropriate to rely on echocardiographic parameters of global RV function such as RVFAC in this context.